Socio-economic predictors of undernutrition and anaemia in adolescent mothers in West and Central Africa - Sagalova, Vera; Vollmer, Sebastian; Ntambi, John; Sodjinou, Roger; Simen-Kapeu, Aline; Bärnighausen, Till; Zagre, Noel Marie; Nanama, Simeon (Journal of global health, 2021)
Background Adolescence is a formative period when an individual acquires physical, cognitive, emotional, and social resources that are the foundation for later life, health, and well-being 111. However, in West and Central African region, this trajectory is curtailed by early childbearing associated with an increased risk of undernutrition and anemia. Evidence on socio-economic determinants of anemia and undernutrition in adolescent mothers is limited. This paper aims to shed some light on this issue and, more specifically, assess the socio-economic determinants of anemia among childbearing adolescents in the region. Methods For this observational study, we pooled data from all Demographic and Health Surveys (DHS) conducted in countries in West and Central Africa region between 1986 and 2017. Outcomes were undernutrition and anemia in adolescent mothers. Predictors were education, wealth, place of residence (rural/ urban), and religion. Descriptive statistics were calculated using survey weights for individual surveys and in the pooled sample each country was additionally weighted with its population share. We estimated multiple regression models with and without primary sampling unit fixed effects for both outcomes. All regressions were linear probability models. Results Having no formal education was the strongest predictor for both anemia and undernutrition. Belonging to the richest asset quintile was also associated with lower anemia and undernutrition prevalence in some specifications. While urban location of the mother was positively associated with anemia, there was no association with undernutrition. Conclusions Overall, having any formal education emerged as a sole strong predictor of reduced adolescent maternal undernutrition and anemia. Promotion of female education can potentially serve as a high-impact intervention to improve adolescent girls' health in the region. However, we cannot make conclusions about its causal impact based on this study alone.